Innovation and leadership in parliamentary process: Case about vitro fertilisation debate - Zúñiga Rámirez, César (2014)
This article examines the Costarican parliamentary discussion of in vitro fecundation, on its first stage, from the point of view of innovation and leadership. In an interdisciplinary approach which integrates conceptual tools from Political Science and Administration, the study suspects that the parliamentary debate of the topic of interest is trapped in a not much innovative discussion and a very low leadership profile which ended up in a “loss-loss” decision. From this analysis the article concludes with a discussion of a model of political management proposal in order to guide the parliament debate of sensitive topics, taking advantage of assertive innovation and leadership.